2022
DOI: 10.1186/s12904-022-01032-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of the death literacy index and benchmarking of death literacy level in a representative uk population sample

Abstract: Background Death literacy includes the knowledge and skills that people need to gain access to, understand, and make informed choices about end of life and death care options. The Death Literacy Index (DLI) can be used to determine levels of death literacy across multiple contexts, including at a community/national level, and to evaluate the outcome of public health interventions. As the first measure of death literacy, the DLI has potential to significantly advance public health approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Understanding the concept of death and having relevant knowledge on the topic de nes one's level of death literacy [10,11]. Studies on death literacy, which is a new concept in the literature, are limited [14]. In a community study on death literacy in the United Kingdom, it was reported that the death literacy of the participants was close to the middle level [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the concept of death and having relevant knowledge on the topic de nes one's level of death literacy [10,11]. Studies on death literacy, which is a new concept in the literature, are limited [14]. In a community study on death literacy in the United Kingdom, it was reported that the death literacy of the participants was close to the middle level [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Death literacy, which is a new concept in academia, is de ned as the knowledge and skills people need to access, understand, and make informed decisions about death and end-of-life care options [12]. However, studies on death literacy are limited [13,14]. Understanding death and learning the unknowns about death are especially important in improving the quality of life of patients with life-threatening chronic diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…This measure is used to assess the knowledge and skills that enable people to gain access to, to understand, and to make informed choices about death and end-of-life care options. This notion serves as an index that can be used to predict the death quality of individuals as well as to reflect the overall quality of public health palliative care [ 33 ]. DLI is a 29-item scale comprising 4 subscales: ‘Practical Knowledge’ (8 items), ‘Experiential Knowledge’ (5 items), ‘Factual Knowledge’ (7 items) and ‘Community Knowledge’ (9 items).…”
Section: Methodsmentioning
confidence: 99%
“…Total DL is calculated as a higher-order composite score, which is said to reflect overall capacity gained from previous experiences [ 6 ]. The proposed six-factor model in the original English-language DLI demonstrated satisfactory psychometric properties in Australia indicating good model fit overall (CFI = 0.955, TLI = 0.95, RMSEA = 0.049), and high reliability of the scales and sub-scales (Cronbach’s α ranging 0.82 to 0.95) [ 2 ], and the United Kingdom (CFI = 0.94, RMSEA = 0.07, SRMR = 0.07; Cronbach’s α for sub-scales ranging 0.76 to 0.93) [ 7 ]. Moreover, translated DLI versions have demonstrated acceptable reliability and validity in Turkey (total CVI = 0.91; CFI = 0.93, RMSEA = 0.053; Cronbach’s α ranging 0.68–0.90) [ 8 ] and China (CFI = 0.956, RMSEA = 0.055, SRMR = 0.051, Cronbach’s α for sub-scales ranging 0.76–0.97) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…As such, the DLI may constitute a promising tool for appraising impact of health promoting activities in relation to EOL issues. To date, the DLI has primarily been used among adults in the Australian general public, although the questionnaire has garnered increasing interest internationally, and been validated in the United Kingdom [ 7 ], Turkey [ 8 ], and China [ 9 ]. However, the extent to which DL and its operationalization are comparable across cultures is unknown.…”
Section: Introduction and Aimmentioning
confidence: 99%